Religion, Local Wisdom, and Power of The Madurese Society: Islamic Perspective and Social Theory - Takdir, Mohammad; Roibin, Roibin; Sumbulah, Umi (el Harakah: Jurnal Budaya Islam, 2024)
This research aims to elucidate the relationship between religion, local wisdom, and power relations in the dynamics of Madurese community life from an Islamic perspective, religious scripture texts, and social theory. The research employs qualitative methods focusing on the Madura community as a distinct ethnic group in conducting social interactions and identifying language expressions that symbolize everyday peace. This study employs various data collection methods, including observation, interviews, and documentation. A thorough examination of the dynamics of religion, traditional knowledge, and power dynamics within the Madurese community serves as the data analysis technique employed in this study. By focusing on ontological and epistemological issues, this research utilizes social theory and an Islamic viewpoint to conceptually explain the study of religion, local wisdom, and power relations. The findings show that the Madurese people are known for their unwavering commitment to togetherness, balance, peace, and harmony. This is reflected in 'rampak naong bringen korong,' a concept of local wisdom that represents their deeply ingrained cultural values and moderate religious teachings. These insights hold implications for further studies in exploring the practical applications of local wisdom in promoting social cohesion, governance effectiveness, and community well-being. Penelitian ini bertujuan untuk menjelaskan hubungan antara agama, kearifan lokal, dan hubungan kekuasaan dalam dinamika kehidupan masyarakat Madura dari perspektif Islam, teks-teks agama, dan teori sosial. Penelitian ini menggunakan metode kualitatif yang berfokus pada komunitas Madura sebagai kelompok etnis yang berbeda dalam melakukan interaksi sosial dan mengidentifikasi ekspresi bahasa yang melambangkan perdamaian sehari-hari. Studi ini menggunakan berbagai metode pengumpulan data, termasuk observasi, wawancara, dan dokumentasi. Pemeriksaan menyeluruh terhadap dinamika agama, pengetahuan tradisional, dan dinamika kekuasaan dalam komunitas Madura berfungsi sebagai teknik analisis data yang digunakan dalam penelitian ini. Dengan memfokuskan pada isu ontologis dan epistemologis, penelitian ini menggunakan teori sosial dan sudut pandang Islam untuk menjelaskan secara konseptual studi tentang agama, kearifan lokal, dan hubungan kekuasaan. Temuan menunjukkan bahwa masyarakat Madura dikenal karena komitmennya yang teguh terhadap kebersamaan, keseimbangan, perdamaian, dan harmoni. Hal ini tercermin dalam 'rampak naong bringen korong,' sebuah konsep kearifan lokal yang mewakili nilai-nilai budaya mereka yang sangat tertanam dan ajaran agama yang moderat. Temuan ini memiliki implikasi untuk penelitian lebih lanjut dalam mengeksplorasi aplikasi praktis kearifan lokal dalam mempromosikan kohesi sosial, efektivitas tata kelola, dan kesejahteraan masyarakat.